Experimental Investigation on Seismic Behaviours of Reinforced Concrete Columns under Simulated Acid Rain Environment - Hao Zheng; Shansuo Zheng; Yixin Zhang; Yonglong Cai; Ming Ming; Jingliang Zhou (Advances in Civil Engineering)
The purpose of this paper was to systematically investigate the influence of acid rain environments on the seismic behaviour of a reinforced concrete (RC) column. Six RC column specimens with shear span ratios of 2.84 were tested under low cyclic reversed loads after being subjected to accelerated corrosion tests in an artificial climate. The corrosion level and stirrup ratio were used as the control variables. The corrosion ratios of the longitudinal rebars ranged from 0 to 13.17%, and the corrosion ratios of the stirrups varied from 0 to 6.75%. The seismic behaviours of the column specimens were analysed with respect to visual damage, failure mode, hysteresis behaviour, load-carrying capacity, deformation capacity, stiffness degradation, and energy dissipation behaviour. The test results showed that the appearance characteristics of the six column specimens exhibited varying degrees of visual damage as a result of the simulated acid rain exposure. All six specimens were dominated by similar flexural-shear failures under low cyclic reversed loads, regardless of the distinctions in the corrosion levels or stirrup ratios. For the specimens with the same ratios of stirrup, as the corrosion level increased, the load-carrying capacity, deformation capacity, stiffness, and energy dissipation capacity were continuously decreased. For the specimens with the same levels of corrosion, the higher the stirrup ratio was, the stronger the restraint effect of the stirrups on the concrete, and the seismic behaviours of the specimens were obviously improved.